Peran Inovasi Keuangan dalam Meningkatkan Akses ke Layanan Ekonomi di Masyarakat - Sita Dian Afsari; M. Zidny Nafi’ Hasbi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Financial innovation plays a crucial role in increasing people's access to economic services, especially in the ever-evolving digital era. Through various forms of innovation such as digital financial services, fintech, mobile banking, and electronic payment systems, people, including those in remote areas—have made it easier to reach banking, investment, and financing services. These innovations help overcome various conventional barriers, such as limited physical infrastructure, high transaction costs, and the unaffordability of formal financial services. In addition, the presence of financial technology also expands financial inclusion by providing products and services that are more flexible, cheap, and easily accessible through mobile devices. This not only encourages local economic growth, but also empowers micro, small, and medium enterprises (MSMEs) to develop their businesses. However, challenges remain, such as the need for financial literacy, consumer data protection, and adequate regulatory oversight. Therefore, synergy between the government, financial institutions, technology providers, and the community is important to ensure that financial innovation can be utilized optimally and sustainably in promoting inclusive economic prosperity. Financial innovation is not just a technological advancement, but a strategic solution towards economic justice.